Interrater Reliability of Palpation of Myofascial Trigger Points in Three Shoulder Muscles - Bron, Carel (Journal of Manual & Manipulative Therapy, Inc., 2007)
This observational study included both asymptomatic subjects (n=8) and patients with unilateral or bilateral shoulder pain (n=32). Patient diagnoses provided by the referring medical physicians included subacromial impingement, rotator cuff disease, tendonitis, tendinopathy, and chronic subdeltoid-subacromial bursitis. Three raters bilaterally palpated the infraspinatus, the anterior deltoid, and the biceps brachii muscles for clinical characteristics of a total of 12 myofascial trigger points (MTrPs) as described by Simons et al. The raters were blinded to whether the shoulder of the subject was painful. In this study, the most reliable features of trigger points were the referred pain sensation and the jump sign. Percentage of pair-wise agreement (PA) was ≥ 70% (range 63–93%) in all but 3 instances for the referred pain sensation. For the jump sign, PA was ≥ 70% (range 67–77%) in 21 instances. Finding a nodule in a taut band (PA = 45–90%) and eliciting a local twitch response (PA = 33–100%) were shown to be least reliable. The best agreement about the presence or absence of MTrPs was found for the infraspinatus muscle (PA = 69–80%). This study provides preliminary evidence that MTrP palpation is a reliable and, therefore, potentially useful diagnostic tool in the diagnosis of myofascial pain in patients with non-traumatic shoulder pain.